Deffis, Emilia. Figuraciones de lo ominoso. Memoria histórica y novela postdictatorial (Anclajes, 2012)
Reseña crítica de Deffis, Emilia. Figuraciones de lo ominoso. Memoria histórica y novela postdictatorial